Filipino use of Medicinal Plants in Selected Literary Genres: A Reflection of Tradition - Dimaano, Matilda H. (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Literature in its various narrative forms (e.g. novel, legend etc.) reflects human society and culture, of which the latter comprising a whole complex of human behavior learned by people, can and is inherited across generations. One of these cultural traditions is the use of medicinal plants as cure for sicknesses which finds documentation in literary works among early Filipinos and carry the belief up to the present time. Using the four narratives consisting of three full -length novels and a legend as literary sources, the study determined the types of plants traditionally used to cure various sicknesses among Filipino communities, identified the kind of sickness cured by the plants, and presented insights gleaned from such exposition. The different medicinal plants mentioned in the narratives include the alugbati or Malabar nightshade or spinach (Basella alba/Basella rubra), Atis or Custard apple (Annona squamosa), Dampimbanal or holytouch (Hierochloe borealis/Hierochloe odorata), Banaba (Lagerstroemia speciosa) and tamarind fruit (Tamarindus indica). In the novels, Alugbati leaves together with tamarind juice was mentioned as remedy for psychosomatic symptoms associated with adolescent’s stress from the onset of manhood. Custard apple leaves was mentioned as cure for body aches and pains, while Dampimbanal or holytouch was used as a relief for fractured bones. The plant parts of Banaba were mentioned to help address different internal disorders, like an ailing kidney, and problems related to the urinary tract and the stomach. In the legend, tamarind was mentioned to be a cure for colds. Some of the insights gleaned from this study are the renewed appreciation and valuation of the knowledge gained in the use of medicinal plants as cure for various illnesses among Filipinos in the context of conservation of cultural tradition, biodiversity and community health care and drug development, the awakening of the awareness and interest of the younger generation on the usefulness of medicinal plants as cure of sickness and their subsequent motivation, and the appreciation of respect for other peoples’ traditions, knowledge gained on various medicinal plants and their uses which could have direct value in addressing ailments in their own homes.